Quality improvement of noodles fortified with moringa leaf powder, konjac glucomannan, and acetylated starch - Nguyễn Minh Thủy; Tran Ngoc Giau; Vo Quoc Tien; Hong Van Hao; Võ Quang Minh; Ngô Văn Tài (Acta Scientiarum Polonorum Technologia Alimentaria, 2023)
1Institute of Food and Biotechnology, Can Tho University, Vietnam 2College of Environment and Natural Resources, Can Tho University, Vietnam 3School of Food Industry, King Mongkut’s Institute of Technology Ladkrabang, Bangkok, Thailand
Keywords: Moringa oleifera research and applications; African Botany and Ecology Studies; Hibiscus Plant Research Studies